2021
DOI: 10.1039/d1ra01007g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and visible-light photocatalytic degradation of Ag3PO4/AgBr/hydroxyapatite ternary nanocomposites prepared from oyster shells

Abstract: A new type of Ag3PO4/AgBr/hydroxyapatite photocatalyst was prepared from oyster shells, which showed high efficiency in the degradation of organic dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…3− ) as Ag 3 PO 4 . All these characteristics provide a strong guarantee for the potential to combine silver phosphate and HAP, and the previous research results of our team also confirmed this view [22]. Although Ag 3 PO 4 composite materials have been studied, ternary Ag 3 PO 4 , g-C 3 N 4 and HAP composite materials have not been reported.…”
Section: Introductionsupporting
confidence: 83%
“…3− ) as Ag 3 PO 4 . All these characteristics provide a strong guarantee for the potential to combine silver phosphate and HAP, and the previous research results of our team also confirmed this view [22]. Although Ag 3 PO 4 composite materials have been studied, ternary Ag 3 PO 4 , g-C 3 N 4 and HAP composite materials have not been reported.…”
Section: Introductionsupporting
confidence: 83%
“…and hydroxide (OH * ) were the reaction intermediates for the photocatalytic degradation process. [52] When considering the addition of AO; there was no discernible change in the degradation process. A plot of effect of different scavengers presented in Figure S1 of SI.…”
Section: Effect Of Initial Concentration Of Antibioticsmentioning
confidence: 98%
“…The rates of degradation of the antibiotics were greatly delayed after the addition of p ‐BQ and IP. It indicated that superoxide (O 2 − ⋅) and hydroxide (OH⋅) were the reaction intermediates for the photocatalytic degradation process [52] . When considering the addition of AO; there was no discernible change in the degradation process.…”
Section: Scavenger Experimentsmentioning
confidence: 99%
“…For the past decades, the researchers are paying much attention to the removal of textile organic pollutants by various methods which include biodegradation, electrocoagulation, photodegradation, oxidation, adsorption, and ultrafiltration [3][4][5][6][7][8]. Among them, photocatalysis has proved to be an excellent method to decompose the organic effluents being highly efficient and cost-effective [9,10]. Due to photocatalytic efficiency and cost-effectiveness, TiO 2 -based photocatalysts have been of research interest yet their practical application is limited because of their higher bandgap energy which falls in the UV region [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ag 3 PO 4 can be undoubtedly an interesting candidate to be studied. Nevertheless, its higher solubility and poor stability hinder its vast application [9]. Ag 3 PO 4 is vulnerable to photocorrosion.…”
Section: Introductionmentioning
confidence: 99%